Paradigm Shift of Science and Technical Education through Open and Distance Education Mode: Exploring the Impact of Open and Distance Education on Science and Technical Education (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is an important instrument for social and economic change and an investment for better future. It is a lifelong process. It should cater to the needs of those who need to further knowledge and skills for various reasons. Distance Education is an innovative and flexible system for imparting education to varied target groups at different stages. At present, the youth and women are enrolling in higher number into Distance mode.